IMPLEMENTASI PENGELOLAAN BARANG BUKTI TINDAK PIDANA DI WILAYAH HUKUM POLRESTA PEKANBARU - Muhardi, Dekky; Harahap, Irawan; Pardede, Rudi (LPPM STIH Awang Long, 2025)
In the jurisdiction of the Pekanbaru City Police Resort, as part of the Indonesian National Police tasked with maintaining public security and order, the management of criminal evidence should be carried out professionally, transparently, and in accordance with applicable legal provisions, as stipulated in the Indonesian Criminal Procedure Code (KUHAP), the Indonesian Criminal Code (KUHP), and internal police regulations. The purpose of this research is to analyze the implementation of criminal evidence management within the jurisdiction of the Pekanbaru City Police Resort, to examine the obstacles in its implementation, and to explore efforts to overcome these obstacles. The research method used is sociological legal research. Based on the research findings, it is known that the implementation of criminal evidence management in the jurisdiction of the Pekanbaru City Police Resort has not been running as it should. Although the formal procedures for managing evidence have been regulated through procedural law and internal police regulations, in practice, some pieces of evidence are still being stored within individual units rather than in centralized, standardized facilities. The obstacles in implementing evidence management include lack of coordination between investigators and other relevant units involved in the criminal justice process, inadequate infrastructure and storage facilities, and the absence of an optimal internal supervision system over evidence management processes. Efforts to overcome these challenges include strengthening inter-departmental coordination, encouraging the digitization of evidence administration systems, improving physical storage facilities, and pushing for adequate budget allocation from the police institution as well as support from local governments to ensure that evidence storage facilities meet ideal standards. Additionally, enhancing the integrity and professionalism of personnel involved in the management of criminal evidence is also a crucial measure.